Genistein sensitizes sarcoma cells in vitro and in vivo by enhancing apoptosis and by inhibiting DSB repair pathways - Liu, X.X. (Oxford University Press, 2016)
The aim of this work was to investigate the radiosensitization effects of genistein on mice sarcoma cells and the corresponding biological mechanisms in vitro and in vivo. Using the non-toxic dosage of 10 μM genistein, the sensitizer enhancement ratios after exposure to X-rays at 50% cell survival (IC50) was 1.45 for S180 cells. For mice cotreated with genistein and X-rays, the excised tumor tissues had reduced blood vessels and decreased size and volume compared with the control and irradiation-only groups. Moreover, a significant increase in apoptosis was accompanied by upregulation of Bax and downregulation of Bcl-2 in the mitochondria, and lots of cytochrome c being transferred to the cytoplasm. Furthermore, X-rays combined with genistein inhibited the activity of DNA-PKcs, so DNA-injured sites were dominated by Ku70/80, leading to incompleteness of homologous recombination (HR) and non-homologous end-joining (NHEJ) repairs and the eventual occurrence of cell apoptosis. Our study, for the first time, demonstrated that genistein sensitized sarcoma cells to X-rays and that this radiosensitizing effect depended on induction of the mitochondrial apoptosis pathway and inhibition of the double-strand break (DSB) repair pathways.